Exploring willingness-to-pay for ‘malaria-free’ rice among rural consumers in Rwanda: examining the potential for a local voluntary standard - Alexis Rulisa; Luuk van Kempen; Dirk-Jan Koch (Agricultural and Food Economics, 2023)
Abstract Rice cultivation in Sub-Saharan Africa produces a negative externality in the form of higher malaria risk. Larval source management, such as the application of bio-larvicides in rice fields, is available to mitigate the problem. However, the cost of larvicide and the corresponding spraying campaigns is such that rice farmers are unable to carry all of the financial burden themselves. This study explores in a rice-growing area of Rwanda whether, and to what extent, local consumers are willing to share this burden through their consumption choices. In a non-incentivized format, we elicit willingness-to-pay from 290 respondents for locally produced rice that is cultivated in either sprayed or non-sprayed fields. Price premium estimates are extracted to discuss the prospects of a voluntary sustainability standard for ‘malaria-free’ rice. We observe robust support among local consumers to re-align food production and public health through the marketplace. The results thus warrant a critical reflection on the assumption in the ethical consumption literature that consumers in the Global South, especially those on low incomes in rural areas, cannot play their part.